2021
DOI: 10.1021/acs.chemmater.1c00339
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Li+ and Anion Diffusivities in Polyacetal Electrolytes: A Pulsed-Field-Gradient NMR Study of Ion Self-Diffusion

Abstract: Polyacetal electrolytes have been demonstrated as promising alternatives to liquid electrolytes and PEO for rechargeable lithium-ion batteries; however, the relationship between polymer structure and ion motion is difficult to characterize. Here, we study structure-property trends in ion diffusion with respect to polymer composition for a systematic series of five polyacetals with varying ratios of ethylene oxide (EO) to methylene oxide (MO) units, denoted P(xEO-yMO), and PEO. We first use 7 Li and 19 F pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…Amongst the various polymer chemistries investigated for SPE application, those comprising of polyethylene oxide (PEO) with various lithium salts have undoubtedly received the most interest, however recent studies of similar polyethers and polyacetals have also been reported by Balsara and Coates. 9–13 Despite high ionic conductivity ( ca. 10 −3 S cm −1 at 70 °C) above the melting temperature of PEO, poor room temperature performance, high crystallinity and low lithium transference numbers (typically around 0.2) of PEO-based SPEs remain a limitation to their practical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the various polymer chemistries investigated for SPE application, those comprising of polyethylene oxide (PEO) with various lithium salts have undoubtedly received the most interest, however recent studies of similar polyethers and polyacetals have also been reported by Balsara and Coates. 9–13 Despite high ionic conductivity ( ca. 10 −3 S cm −1 at 70 °C) above the melting temperature of PEO, poor room temperature performance, high crystallinity and low lithium transference numbers (typically around 0.2) of PEO-based SPEs remain a limitation to their practical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A series of such polyacetals with varying ratios of EO and MO in the repeat units, P(nEO-mMO), were synthesized 36 and systematically studied electrochemically 37 and through pulsed-field-gradient nuclear magnetic resonance spectroscopy measurements and MD simulations. 36 The polymers studied previously were P(EO-2MO), P(EO-MO), P(2EO-MO), P(3EO-MO), and P(4EO-MO) compared to PEO with LiTFSI salt. Polyacetal−LiTFSI SPEs were studied at similar reduced temperatures (T − T g ) as the glasstransition temperatures in the presence of LiTFSI varied significantly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous work, , the design strategy that was employed was to maintain a high oxygen-to-carbon ratio (p) in the backbone of the polymer to provide sufficient well-connected solvation sites for the Li cation by incorporating methylene oxide (O–CH 2 or MO) repeat units into the polymer backbone along with ethylene oxide (O–CH 2 –CH 2 or EO). A series of such polyacetals with varying ratios of EO and MO in the repeat units, P­( n EO- m MO), were synthesized and systematically studied electrochemically and through pulsed-field-gradient nuclear magnetic resonance spectroscopy measurements and MD simulations . The polymers studied previously were P­(EO-2MO), P­(EO-MO), P­(2EO-MO), P­(3EO-MO), and P­(4EO-MO) compared to PEO with LiTFSI salt.…”
Section: Introductionmentioning
confidence: 99%
“…x-3 the ratio of Li + cations to O atoms within tetraglyme [30][31][32]. For these electrolytes, the cation, anion, and solvent may be selectively and unambiguously probed with 7 Li, 19 F, and 1 H NMR measurements, respectively.…”
mentioning
confidence: 99%